2016
DOI: 10.1093/europace/euv418
|View full text |Cite
|
Sign up to set email alerts
|

Multiple leadless pacemakers implanted in the right ventricle of swine

Abstract: Multiple leadless pacemakers implanted in the RV do not appear to impact cardiac function. Therefore, it appears safe to implant multiple leadless pacemakers in the same heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…Previous studies examined the feasibility of implanting multiple intra-cardiac devices in the right ventricle. Chen et al 1 already showed that the implantation of two adjacent leadless pacing devices in a swine heart does not lead to dimensional or functional cardiac abnormalities. Omdahl et al 2 implanted three leadless pacemakers in a human cadaver heart (right ventricular apex, mid-septum, and outflow tract).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined the feasibility of implanting multiple intra-cardiac devices in the right ventricle. Chen et al 1 already showed that the implantation of two adjacent leadless pacing devices in a swine heart does not lead to dimensional or functional cardiac abnormalities. Omdahl et al 2 implanted three leadless pacemakers in a human cadaver heart (right ventricular apex, mid-septum, and outflow tract).…”
Section: Discussionmentioning
confidence: 99%
“…implanted two Micra TPS within 1 month in 14 pigs. 13 Of all pigs that underwent implantation procedures, five animals died prior to the end of the 6-month follow-up. Echocardiography was performed at baseline, at second implantation, and at the end of the 6-month follow-up.…”
Section: Nanostim Leadless Pacemakermentioning
confidence: 99%
“…Preclinical studies using swine and human cadaver hearts have demonstrated the feasibility of multiple right-ventricular Micra implants without affecting cardiac function. 32,33 ■ OTHER LIMITATIONS AND CAUTIONARY NOTES At present, leadless pacing is approved for single-chamber right-ventricular pacing. In the developed world, single right-ventricular pacing modes account for only 20% to 30% of new pacemaker implants, which total more than 1 million per year worldwide.…”
Section: Kiehl and Cantillonmentioning
confidence: 99%